Evaluation of Digital Technology Integration in Islamic Religious Education Curriculum: Analysis of Documents and Learning Media - Sheila Mafaizah; Siti Fatmawati; Khairuddin Manurung; Opik Taupik Kurahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to evaluate the integration of digital technology in the Islamic Religious Education (PAI) curriculum and learning media, specifically in KMA No. 183 and 184 of 2019. The background of this research is based on the demands of digitalization in education, which require a balance between technology, pedagogy, and Islamic values. The method used was a qualitative approach with document analysis and observation of digital learning media such as LMS, e-modules, interactive videos, and podcasts. Data were analyzed using the Miles and Huberman model through the stages of reduction, presentation, and conclusion drawing. The results show that digital technology integration has been normatively accommodated in the curriculum and is beginning to be implemented in learning practices through various interactive digital media. However, its implementation is not optimal due to its implicit nature in basic competencies, limited teacher digital literacy, and a lack of strengthening of students' digital ethics. Conclusion: The success of digital technology integration in PAI depends heavily on the balance between Islamic content, pedagogy, and technology (TPACK), as well as the strengthening of spiritual values and digital ethics in the learning process.